Less-cash or more-cash? Determinants and trends of currency in circulation in a panel of 17 economies - Kumar Chandrakamal; Pramod Kumar (Charles University in Prague, Institute of Economic Studies (IES), 2023)
Digital payments are growing rapidly, and the use of cash seems to be declining, at least in advanced economies in Europe and the U.S. However, the literature on payment systems provides an interesting perspective- cash, or currency, when measured as a percentage of the gross domestic product, has not been falling as clearly as might be intuited. Contrarily, many economies face an increase in currency in circulation rates. This paper discusses this topic in literature and explores the determinants of currency in circulation in a panel of 17 countries between 2001-2022 and whether determinants from prior literature are also significant across a group of heterogeneous countries. Interest rates are found to affect the demand for cash significantly and negatively, while tax revenues have a significantly positive impact. Some measures of financial development are also considered but are found to not have any strong explanatory power. Country fixed effects regression analysis suggests that determining what type of economies may have higher or lower currency in circulation is a complex matter requiring more detailed investigation.
Keywords: E12; E41; E50; E51; 330; Currency in circulation; Monetary demand; Panel data; Fixed-effects regression; Interest rates; tax revenue